Cloning, expression and molecular analysis of Iranian Brucella melitensis Omp25 gene for designing a subunit vaccine - Soheil Yousefi; Mojtaba Tahmoorespur; Mohammad Hadi Sekhavati (Wolters Kluwer Medknow Publications, 2016)
Brucellosis is a well-known domestic animal infectious disease, which is caused by Brucella bacterium. The outer membrane protein 25 kDa (Omp25) gene plays an important role in simulating of TNF-α, IFN-α, macrophage, and cytokines cells. In the current study molecular cloning and expression analysis of Omp25 gene for designing a subunit vaccine against Brucella was investigated. Amplifying the full length of candidate gene was performed using specific primers. Sub-cloning of this gene conducted using pTZ57R/T vector in TOP10F`strain of Escherichia coli(E.coli) as the host. Also, pET32(a) + vector used for expression in BL21 (DE3) strain of E.coli. Omp25 gene with 642 bp size was amplified and cloned successfully. The expression results were confirmed by sequencing and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analyses which showed 42 kDa protein band correctly. Also, phylogenic analysis showed this gene has a near genetic relation with other Brucella strains. According to our results we can propose this gene as a candidate useful for stimulation of cell-mediated and humoral immunity system in future study.